Location, Location, Location: Is Membrane Partitioning Everything When It Comes to Innate Immune Activation? - Martha Triantafilou; Philipp M. Lepper; Robin Olden; Ivo de Seabra Rodrigues Dias; Kathy Triantafilou (Hindawi Limited, 2011)
In the last twenty years, the general view of the plasma membrane has changed from a homogeneous arrangement of lipids to a mosaic of microdomains. It is currently thought that islands of highly ordered saturated lipids and cholesterol, which are laterally mobile, exist in the plane of the plasma membrane. Lipid rafts are thought to provide a means to explain the spatial segregation of certain signalling pathways emanating from the cell surface. They seem to provide the necessary microenvironment in order for certain specialised signalling events to take place, such as the innate immune recognition. The innate immune system seems to employ germ-lined encoded receptors, called pattern recognition receptors (PRRs), in order to detect pathogens. One family of such receptors are the Toll-like receptors (TLRs), which are the central "sensing" apparatus of the innate immune system. In recent years, it has become apparent that TLRs are recruited into membrane microdomains in response to ligands. These nanoscale assemblies of sphingolipid, cholesterol, and TLRs stabilize and coalesce, forming signalling platforms, which transduce signals that lead to innate immune activation. In the current paper, we will investigate all past and current literature concerning recruitment of extracellular and intracellular TLRs into lipid rafts and how this membrane organization modulates innate immune responses.